Long-term outcomes of endovenous laser ablation and conventional surgery for great saphenous varicose veins. Issue 13 (22nd August 2018) - Wallace, T; El-Sheikha, J; Nandhra, S; Leung, C; Mohamed, A; Harwood, A; Smith, G; Carradice, D; Chetter, I
Abstract: Background: Clinical guidelines recommend endovenous laser ablation (EVLA) over surgery based on short-term evidence, yet there are few studies reporting mid- to long-term outcomes. The aim of this study was to report the 5-year outcomes from an RCT of surgery versus EVLA for treatment of symptomatic great saphenous varicose veins. Methods: Patients with symptomatic varicose veins due to great saphenous vein (GSV) incompetence were followed up 5 years after enrolment in a randomized trial of either surgery (saphenofemoral junction ligation, GSV strip to the knee and multiple avulsions of varicosities) or EVLA plus multiple avulsions. Outcomes included: clinical recurrence, defined as new varicose veins greater than 3 mm in diameter; Venous Clinical Severity Score (VCSS); quality of life measured by means of Short Form 36, EuroQol Five Dimensions (EQ-5D™) and Aberdeen Varicose Vein Questionnaire (AVVQ); patient satisfaction; and duplex ultrasound examination (DUS) findings. Results: Some 218 of the 276 patients enrolled in the trial (79·0 per cent) were available for follow-up. Clinical recurrence was more frequent following surgery than EVLA at 5 years (34·3 versus 20·9 per cent; P = 0·010). Both groups demonstrated sustained significant improvements at 5 years over baseline in VCSS (surgery: median (i.q.r.) 1 (0–2) from 4 (3-5), P < 0·001; EVLA: 0 (0–1) from 4 (3-5), P < 0·001), AVVQ (surgery: 4·59 (0·56–9·78) from 13·69 (9·81–18·11), P < 0·001; EVLA: 3·35 (0·17 to 6·55) from 12·73 (9·41–17·32), P < 0·001) and EQ-5D™ (surgery: 1·000 (0·796–1·000) from 0·859 (0·796–1·000), P = 0·002; EVLA: 1·000 (0·796–1·000) from 0·808 (0·796–1·000), P = 0·002). VCSS was better for EVLA than surgery at 5 years ( P = 0·031). Technical success assessed by DUS remained high at 5 years (85·4 per cent for surgery and 93·2 per cent for EVLA; P = 0·074). DUS-detected anatomical patterns of recurrence differed between the groups. Conclusion: EVLA was more effective than surgery in preventing clinical recurrence 5 years after treatment of great saphenous varicose veins. Patient-reported outcome measures were similar. Registration number: NCT00759434 (http://www.clinicaltrials.gov ). Abstract : Lower recurrence at 5 years after laser